A Novel Approach on Communication between Blind, Deaf and Dumb People using flex Sensors and Bluetooth - Viswanathan G, Kasi; Seelan C, Sathya; Praveen Kumar, S (International Journal of Engineering and Technology, 2018)
The recent development in many technologies have been playing a major role in satisfying peopleâ€™s lives for their daily need. But still few people are suffering due to some problems. They are blind, deaf and dumb people who are unable to communicate properly with others or among themselves. And we know that there are millions of people who are blind, deaf and dumb in this world. And we know that they use sign language to communicate but only few people can be able to understand. So this project introduces a system that can be used to improve the communication among blind, deaf and dumb people. This project introduces an idea that communication can be done using flex sensors and Bluetooth using ARDUINO boards. Flex sensors are fixed with the gloves such that it can be bent along with the movement of fingers and then it is connected to ARDUINO. Then LCD and Audio Playback Recorder module is connected to ARDUINO and then coding is done such that if flex sensor is bent, a specified message is displayed on LCD and can be played in speaker through APR module. Here coding is done using a software ARDUINO IDE. We can also send text message through android smart phone which will be displayed on LCD, this can be done by connecting Bluetooth module to ARDUINO and message can be sent through an app by connecting to Bluetooth. We are also using GPS module to track the present location which will be displayed on LCD in terms of latitude and longitudinal degrees.Â Â